2016
DOI: 10.1063/1.4964718
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of multiexponential fluorescence decays from 2-aminopurine-labeled dinucleotides

Abstract: The fluorescent probe 2-aminopurine (2Ap) has been used for decades to study local conformational fluctuations in DNA. Steady-state and time-resolved measurements of 2Ap fluorescence have been used to predict specific conformational states through suitable modeling of the quenching of the fluorescence of a 2Ap residue incorporated site-specifically into a DNA strand. The success of this approach has been limited by a lack of understanding of the precise factors responsible for the complex, multiexponential dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Ultrafast transient absorption reports on dynamical processes that occur on a fs-ns timescale and as such allow correlations between structure and population dynamics. The quenching of the excited singlet (S 1 ) state population in 2AP is widely recognized to occur by electron transfer when 2AP is stacked with another nucleic acid base,[32, 33] and the photophysical aspects of the charge transfer mechanism, as well as the origin of the multiphasic decay lifetimes, have been discussed in detail elsewhere[3438]. Of importance to this work, the transient absorption signal reports on the distance-dependent charge recombination dynamics that follows the charge transfer quenching event between the 2AP and its adjacent nucleobases[37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrafast transient absorption reports on dynamical processes that occur on a fs-ns timescale and as such allow correlations between structure and population dynamics. The quenching of the excited singlet (S 1 ) state population in 2AP is widely recognized to occur by electron transfer when 2AP is stacked with another nucleic acid base,[32, 33] and the photophysical aspects of the charge transfer mechanism, as well as the origin of the multiphasic decay lifetimes, have been discussed in detail elsewhere[3438]. Of importance to this work, the transient absorption signal reports on the distance-dependent charge recombination dynamics that follows the charge transfer quenching event between the 2AP and its adjacent nucleobases[37].…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the longer component is due to a small fraction of misfolded RNA and in our fitting analyses the lifetime of this species was fixed to 10 ns (see materials and methods), a value consistent with that of isolated 2AP nucleoside in aqueous solution[39]. The distribution of lifetimes extracted from the transient decay signals may be understood by invoking a basic distance-dependent charge recombination model[38, 40] according to which 2AP in the bulge undergoes charge recombination with the closest nucleobase at a rate that depends exponentially on their mutual separation. Conformations in which 2AP and the adjacent nucleobases are oriented closer together undergo hundreds of femtoseconds charge recombination (τ 1 ), whereas those oriented in a way that increase the interbase distance undergo intermediate, picosecond dynamics (τ 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, when 2Ap is incorporated into a DNA strand, its emission is strongly quenched, and the measured emission signals exhibit multiple exponential decay components. This complexity is already observed in dinucleoside monophosphates (DNMPs), the shortest possible DNA strands with just two interacting nucleosides joined by a phosphate group. For example, studies of 2Ap-labeled single-stranded DNA dinucleotides show that three to five exponentials are needed to fit the measured emission signals between 100 ps and 50 ns. , Even though the 2Ap fluorophore interacts with only a single nucleobase to which it is joined via the usual phosphate linkage found in nucleic acids, detailed understanding of the mechanisms responsible for fluorescence quenching is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that base stacking quenches fluorescence by a 2Ap label in an oligonucleotide. , The observed complexity of the emission signals likely reflects an underlying diversity of structures, which transition between stacked and unstacked structures over multiple timescales. However, the structures of dinucleotides and DNMPs are commonly considered using two-state models in which the bases are either stacked or unstacked. These models have been used to estimate base stacking and unstacking rates from ultrasound and temperature-jump measurements, , but it is not clear that the resulting rates accurately capture the underlying dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Longer decay times also confirmed that the use of the MgZnO layer not only minimized the J-V hysteresis but also increased the optical quality of the perovskite in sample S2. Four decay times could be assigned to different recombination mechanisms [49] or interpreted with other models such as continuous Lorentzian lifetime distribution [50,51], thermalized stretching of the exponential line shape [52], the stretched exponential (or Kohlrausch decay function), its modified ver-sions according to Eq. (25) in Ref.…”
Section: Resultsmentioning
confidence: 99%